DAMPAK BAHASA GAUL DALAM MEDIA SOSIAL TERHADAP HASIL MENULIS PEMBELAJARAN BIPA - Fauziah, Putri Azani (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This study aims to analyze the impact of slang language, specifically abbreviations, in social media on the learning of Indonesian as a Foreign Language (BIPA). Slang language, which includes abbreviations, word contractions, and informal terms, has become an integral part of daily communication, especially on social media platforms. This phenomenon presents a challenge for BIPA learners, particularly beginners, as slang is often confusing and deviates from standard language rules. In this study, the writings of three BIPA learners with varying proficiency levels were analyzed to identify how slang usage affects their understanding and writing skills. The findings show that learners often struggle to comprehend the meaning and context of slang terms such as "gpp" (nggak apa-apa) and "kalo" (kalau), commonly used in informal conversations. The use of slang results in difficulty writing according to the formal language standards ofIndonesian. Therefore, this study recommends gradually integrating slang language instruction into the BIPA curriculum to help learners overcome the challenges of communicating in everyday social contexts in Indonesia.